Reasons for choosing homeschooling and approaches most used : a qualitative content analysis - Abuzandah, Sameer Ali (Kansas State University, 2021)
The purpose of this content analysis was to review home school literature regarding homeschooling approaches, parents’ motivations for selecting homeschooling and technology integration. The main aim of this study was to use content analysis of some home school literature as a way to determine best practices, approaches, and reasons for choosing a homeschooling approach. The review of literature established that religion and morality, the need to align personal values with environmental and societal values, and school violence and overcrowding were the primary rationale for parents choosing homeschooling. The most common technique used was classical education with cooperative schooling approach. The second approach most commonly used was computer-based homeschooling, followed by the traditional method, followed by the public and private approach. Additionally, this study found that there has been an increase between technology integration and homeschooling, especially in learn and practice approaches, but also in the use of social networking websites to connect homeschooling families with broader networks. Due to the adoption and diffusion of modern technologies, parents have perceived homeschooling as a good option for their families and children. To conclude, through this study, new information was gathered regarding the integration of instructional technology by children learning from home. Therefore, this research study significantly contributes to the existing academic literature on the topic. The study is rich in information that can benefit the current and aspiring homeschoolers by explaining the curriculum amount and available homeschooling opportunities, as well as the benefits and constraints of technology.
Keywords: Homeschooling